Pengembangan Pengembangan Media Big Book Pada Tema Cuaca Hujan Untuk Meningkatkan Literasi Membaca Siswa Kelas III Sekolah Dasar: Pengembangan Media Big Book Pada Tema Cuaca Hujan Untuk Meningkatkan Literasi Membaca Siswa Kelas III Sekolah Dasar - Bela, Nabila; Binti Mirnawati, Lilik; Setiawan, Fajar (Literasi: Jurnal Ilmiah Pendidikan Bahasa, Sastra Indonesia dan Daerah, 2024)
The objective of this research is to create a product in the form of a Big Book that demonstrates quality in terms of validity, practicality, and effectiveness in improving the reading literacy of elementary school students at SDN Wonokusumo V. This research adopts a Research and Development (R&D) approach. In this study, the method utilized is the 4-D model of instructional development developed by Thiagarajan, consisting of four stages: Define, Design, Develop, and Disseminate. However, it is noteworthy that in this research, only the development stage is reached, and the dissemination stage is not implemented. Tests, the media development process, teacher and student response questionnaires, and expert validation are the tools used in this data collection method. The suitability of the instructional media is assessed based on: The Big Book has undergone a significant validation process, obtaining a validation percentage of 96% from media experts and 95% from material experts, both meeting the criteria of "very valid." The practicality of the Big Book media is based on observations conducted by students and teachers during the use of literacy media. These observations also demonstrate how effectively the media supports learning objectives, student engagement, and teacher responses to the use of the Big Book in the literacy context. The average score for all student and teacher activities indicates positive results at 92%, meeting the criteria of "very practical." The effectiveness of student learning is measured by pretest and posttest results, indicating the effectiveness of the Big Book media with a percentage of 90%. Therefore, it can be concluded that observations conducted by teachers and students during the use of the Big Book indicate that the book can be considered a valid, effective, and practical learning tool for improving students' reading skills.